View from the Leopoldsberg (looking to Kloster Neuburg) - Mossman, William, fl. 1840-1864 (engraver):::Creator::::::::::::; Bartlett, William Henry, 1809-1854 (artist) ; Beattie, William, 1793-1875 (author):::Contributor:::::::::::: (London; United Kingdom; Published for the proprietors by Geo. Virtue)
Engraving with a view of the Danube from the Leopoldsberg toward Klosterneuburg in Lower Austria